(untitled) (Fiep Bulletin - online, 2014)
Despite the wide range of measuring instruments in the field of sport and physical activity offered by Ostrow (1996), scarce those who help us to know what are the participative preferences of students when learning Physical Education. Being knowledgeable about what the participative preferences of students are, can offer valuable information applicable to the teaching-learning process (Ellison, Boykin, Tyler, and Dillihunt, 2005). The stated goal was to determine and compare the participative preferences when learning between urban and rural Physical Education students. 562 students from Primary Education (N = 415) and Secondary Education (N = 147) took part in the study. From Those 160 were from rural areas and 402 from urban areas. All of them filled out the Graupera / Ruiz Preferences Scale of Social Interaction in PE Learning (GR) that has 28 items divided into four categories: affiliation, competition, cooperation and individualism. Multivariate analysis showed that there are significant differences depending on the area you live, in individualism and affiliation factors, being the rural zone that score the highest. There are several facts that affect the practice and learning in Physical Education among which the personal and environmental facts are highlighted (Sallis, 1995), understanding this last one as an explanatory element of the results.